Factors influencing for choosing professional courses: a case study of undergratuate students of faculty of management studies and commerce, university of jaffna sri lanka - Thevahi, S.; Luxshana, N.; Pamila, N.; Chamindakumara, P.; Sakeeran, S. (university of Jaffna, 2014)
Nowadays, following a professional course has been a famous trend among the undergraduates. Professional courses can be followed by anyone with minimum qualification. The purpose of this study is to find out the reasons as to why the undergraduates, who are already qualified for a University degree, choose professional courses. The study reveals an empirical examination of factors influencing for choosing professional courses among undergraduate students, faculty of management studies and commerce, University of Jaffna, Sri Lanka. Researchers divided professional courses under the four disciplines such as Accounting, Marketing, Human Resource Management and Financial Management. The study was conducted using survey design st nd with the sample of one hundred, including 01 and 02 Year undergraduate students. Primary and secondary data were used to conduct the study. Sophisticated statistical model as “exploratory factor analysis” (EFA) has been used. The factors investigated included such as high level job opportunities, enhancing field related skills, inspired by the role model, associate with current market & geographical area, fulfil the expectations of organization, high level job remuneration, desire to achieve a mastery in a particular field, influence of friends, improve the knowledge, parents' compulsion, get job abroad, prestige in society, self employment, personal interest and financial background The finding of this study revealed that high level job opportunity plays a major role in choosing professional courses among the undergraduate students.
Keywords: Professional courses; Undergraduates